Risks of Oral and Maxillofacial Surgery in Patients with Thyroid Dysfunction: Proper Management Strategies - Correia Lima, Bernardo; Grillo, Ricardo; Alvarez Quinta Reis, Bruno; Peral Ferreira Pinto, Leonardo Augustus; Melhem-Elias, Fernando (European Journal of Therapeutics, 2024)
Oral and maxillofacial surgery encompasses procedures for correcting mouth, jaw, and facial issues, posing challenges in patients with thyroid dysfunction due to its impact on the coagulation system. Many authors noted a rise in thyroid disease among younger adults, affecting surgeries traditionally performed in this demographic. Thyroid dysfunction alters hemostasis, with hyperthyroidism increasing thromboembolic risks and hypothyroidism impairing wound healing and causing bleeding tendencies. In OMF surgery, hyperthyroid patients face thromboembolic risks, requiring preoperative assessment, thyroid normalization, and anticoagulant prophylaxis. Hypothyroid patients need optimized hormone therapy, careful hemostasis, and postoperative monitoring. Multidisciplinary collaboration among endocrinologists, surgeons, and hematologists is crucial for tailored management strategies. In conclusion, understanding thyroid dysfunction's hemostatic impact is vital for safe OMF surgery, necessitating personalized perioperative care strategies.